3D Corona Discharge Model and Its Use in the Presence of Wind During a Thunderstorm - Guo, Xiufeng; Ji, Ziyu; Gao, Yue; Ding, Jie; Zhang, Ling (Frontiers in Environmental Science, 2022)
In this study, the authors develop a three-dimensional (3D) numerical model for the diffusion of positive corona charges based on a 2D model with a uniform grid to explore the characteristics of corona discharge at a building tip during a thunderstorm in the present of wind. The variable-grid meshing method is used to solve the problems of implementing a large simulation domain for thunder clouds (kilometer scale) and the minute calculations of corona discharges at the tip (centimeter scale) in the 3D numerical simulation. The proposed model has advantages in terms of the acquisition of the parameters of corona charges and the spatial distribution of the electric field(E-field) in the environment. We used positive corona discharge at the tip of a building under a negative thunderstorm, along with three wind fields (horizontal wind, updraft, and downdraft with wind speeds of 10 m/s) as an example. The presence of the wind increased the density of corona charges at the tip, where horizontal wind was the most beneficial for its occurrence. Moreover, the characteristics of distortion of the electric field around the tip were significantly different owing to the different directions of wind. Downdraft led to the maximum enhancement in the E-field above the tip and updraft prompted the minimum increase in it, by only 1.19 times. However, the opposite results were obtained for the enhancement in the spatial range of the charges: The updraft led to the greatest increase in it and the downdraft caused the smallest. Corona charges has apparent shielding effect on the E-field below the tip, and can even change the polarity of the E-field in a small area close to it. The strongest shielding effect on the ground E-field occurred in case of the downdraft, which decreased the E-field to 0.36 times compared with that without the corona charges. On the contrary, corona discharge had the weakest shielding ability on the ground when it met the updraft. Horizontal wind had the largest range of shielding on the ground, of up to 14699.36 m2, while the updraft had the lowest, at only 6170.91 m2.